Tourism Infrastructure Development in Uzbekistan during the Covid-19 Pandemic and Post-Pandemic Period - Norbutaevich, Norchaev Asatullo (European Journal of Life Safety and Stability (2660-9630), 2022)
The research article describes suggestions and recommendations for determining the directions of tourism development in our country during the post-pandemic the COVID-19, in order to determine the directions of development based on the analysis of the work conducted abroad, and to develop new types of tourist services.